2018
DOI: 10.2131/jts.43.697
|View full text |Cite
|
Sign up to set email alerts
|

Silver effects on silkworm, <i>Bombyx mori</i>

Abstract: Silver nanoparticles (Ag-NPs) are known as a noble metal, and owing to their exclusive properties, their use is widespread in consumer products and they are mostly incorporated into food packaging and food contact products. The aim of this work was to evaluate the effects of direct ingestion of Ag-NPs through food to assess their toxicity effects on the growth and development of silkworms at different concentrations (1 mg•L-1 to 100 mg•L-1), in addition to the examination of the distribution of Ag-NPs in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 45 publications
1
5
0
Order By: Relevance
“…Consistent with previous research, a decrease in average insect weight emerged as a common response to heavy metal treatment, attributed to elevated protein, glycogen, and lipid consumption ( 52 ), or a reduction in the anti-damage and self-repair mechanisms ( 21 , 22 , 53 ). In this study, the basal metabolic processes, including “amino sugar and nucleotide sugar metabolism,” “biosynthesis of amino acids,” “glycine, serine and threonine metabolism,” “pentose and glucuronate interconversions,” “ascorbate and aldarate metabolism,” and “retinol metabolism” were significantly affected both in the midgut and fat body.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Consistent with previous research, a decrease in average insect weight emerged as a common response to heavy metal treatment, attributed to elevated protein, glycogen, and lipid consumption ( 52 ), or a reduction in the anti-damage and self-repair mechanisms ( 21 , 22 , 53 ). In this study, the basal metabolic processes, including “amino sugar and nucleotide sugar metabolism,” “biosynthesis of amino acids,” “glycine, serine and threonine metabolism,” “pentose and glucuronate interconversions,” “ascorbate and aldarate metabolism,” and “retinol metabolism” were significantly affected both in the midgut and fat body.…”
Section: Discussionsupporting
confidence: 84%
“…The Chinese Oak silkworm ( Antheraea pernyi ) among the best-known species of wild silkworms has been used as a well-known wild silk moth in sericultural and medicine industry for hundreds of years. Notably, they have seen increased utilization in studies involving heavy metals, with research focusing on the potential toxicity effects of cadmium ( 21 ), silver ( 22 ), uranium ( 23 ), and lead ( 24 ) in vivo . However, there remains a paucity of research specifically addressing Hg exposure processes, which could be pivotal in elucidating the underlying mechanisms of Hg toxicity and tracking out the vital targets for Hg tolerance.…”
Section: Introductionmentioning
confidence: 99%
“…Some et al reported that Ag NPs at concentrations of 10 mg/L fed to silkworms presented no toxic effect, promoting silkworm survival and increasing larvae and cocoon weight while negative effects were observed at the 100 mg/L concentration. Nouara et al fed silkworms with Ag NPs at 1, 10, 25, 50, and 100 mg/L, and no significant toxicity was observed at all concentrations although the highest concentrations promoted histopathological changes in the midgut, altered gene expressions, and interfered in several metabolic pathways. It was also found that the incorporation of Ag NPs on silkworm diet at concentrations less than 400 mg/L can improve larvae growth and cocoon weight, although Ag NPs at a higher concentration (>800 mg/L) can cause larvae death, affecting their protein and metabolic metabolism and reducing resistance to oxidative stress, leading to cell apoptosis and necrosis. , …”
Section: Nanomaterials Fed To Silkworms Toward Functionalization Of S...mentioning
confidence: 99%
“…B. mori is one of the most important domesticated insects due to its great potential as a biotechnological platform to produce recombinant proteins, but also because of its great success as an experimental model organism [92,110]. Due to its extraordinary prospects, a wide range of studies have been performed that accelerated fundamental research and beyond in silkworms.…”
Section: Discussionmentioning
confidence: 99%